Hubungan Kecerdasan Emosional dengan Perilaku Phubbing pada Gen Z - Dako, Amalia; Warastri, Annisa (EduInovasi: Journal of Basic Educational Studies, 2025)
Gen Z is a generation that has been exposed to technology and the internet from an early age. In addition to having a positive impact, advances in technology and information also contribute to a major challenge for Generation Z, namely the increase in the use of smartphones that have no certain limits. This dependence gave birth to phone snubbing or phubbing behavior. The purpose of this study is to determine the relationship between Emotional Intelligence and Phubbing. Respondents in this study were 100 Gen Z. This study uses a correlational quantitative method with simple linear regression analysis. The result of the study is that there is a significant relationship between Emotional Intelligence and Phubbing. The results of the analysis show a negative relationship, meaning that if Emotional Intelligence in individuals increases, the lower the Phubbing behavior. Emotional Intelligence as an independent variable contributes 49.7% influence on Phubbing behavior. Thus, Gen Z with good Emotional Intelligence has self-control, empathy and is able to control the use of smartphones in social interactions.